Pembentukan Karakter Disiplin Anak Melalui Kegiatan Rutin Di PAUD - Fransiska Moi; Ermelinda Nau; Emirensiana Bhebhe; Teresia Benedikta Ito; Hildegardis Ule; Rovina Owa; Maria Saferia Ari; Maria Belicia Ruda; Kornelia Rima Demo; Cresensia Ermelinda Odo; Fransiska Febyola Saja; Faustina Ude; Karmelia Rosfinda Meo Maku (Journal of Teaching and Elementary Education, 2026)
The main focus of this observation was to examine how discipline character in early childhood is developed through a series of daily activities at school. This study employed a qualitative descriptive method using observation, interviews, and documentation techniques. The observation was conducted in five schools, namely TKN Beiposo, PAUD Terpadu Citra Bakti, TKN Harapan Bangsa Koeloda, TKN Pembina Turekisa, and TKK St. Theresia Danga. The observation was carried out over a period of two weeks to examine various routine activities implemented to foster children's discipline. The results showed that discipline character was developed through the habituation of daily activities such as praying together, greeting teachers, lining up before entering the classroom, washing hands, tidying up toys, disposing of trash in the proper place, brushing teeth after meals, wearing uniforms according to the schedule, following teachers' instructions, participating in ice-breaking activities, answering teachers' questions, completing learning tasks, obeying classroom rules, and organizing the classroom after learning activities. These repeated and structured habits were proven to help children understand the importance of orderliness, responsibility, and obedience to rules, thereby enabling disciplinary values to be developed and embedded in children's daily behavior from an early age.